Effectiveness of Administering Red Belt Leaf Extract (Piper Crocatum) Against Aeromonas Hydrophila Bacteria in Vitro - Muhammad Jusril; Arief Prajitno; Mohamad Fadjar (Postgraduate, University of Mataram, 2024)
Diseases caused by pathogenic bacteria such as Aeromonas hydrophila are a major health concern. However, the use of red betel leaves (P. crocatum) can serve as a potential solution to this problem due to their antibacterial properties. This research aimed to study the antibacterial activity of red betel leaf extract (P. crocatum), the structure and character of the bacteria inhibited by the extract, and the bioactive components present in the leaves. The results of the disc test showed that the average zone of inhibition was 14.28 mm, while the MIC test results revealed that a dose of 100 mg/L could inhibit bacterial growth (bacteriostatic). Moreover, the crude extract of red betel leaf (P. crocatum) damaged the cell walls and cell membranes of A. hydrophila bacteria, thereby affecting their character and structure. The UV-VIS analysis of red betel leaf extract (P. crocatum) and FTIR analysis with 96% ethanol absorption indicated the presence of flavonoids, saponins, tannins, and alkaloids. These findings suggest that red betel leaves can be used as a natural remedy to fight bacterial infections caused by pathogenic bacteria such as Aeromonas hydrophila